Formulated Human Resource Planning for PT. Marktel in order to Fulfilling Industrial Growth Opportunity - Putridwini Kamal, Livani; Crestofel Lantu, Donald (The Indonesian Journal of Business Administration, 2016)
Abstract - Infrastructure development is an important aspect to accelerate the development process of a country. Infrastructure is also very important as a driver of economic growth, one of the construction sector. According Yusid Toyib as a Direktur Jenderal Bina Konstruksi Kementerian Pekerjaan Umum dan Perumahan Rakyat (Kempupera), Indonesian construction sector growth is always higher in the amount of 6.97% of the economic growth which has only 5.02%. In 2014, the government allocated more than Rp.118 trillion for the construction of housing sector, road maintenance, traffic lights, and bridges, sanitation and environmental management as well as for the development of water resources. Also in 2014, Indonesian Development of Economic and Finance (INDEF) Ahmad Erani Yustika, explained that Sumatera has the highest percentage for the road construction infrastructure by 29.4%. Based on explanation above, it becomes a great opportunity for PT. Marktel to expand its market because of construction projects including construction traffic lights, will be widely published by the government. So Marktel decided to open new branch office in Medan for more focus to reach Sumatera market. However, PT. Marktel need to keep doing an internal analysis, especially in preparing for the opening of new branch office in Medan. Analyzed it using McKinsey 7S such as strategy, structure, system, shared values, style, staff, and skill. Until the problems are found on each aspect. Problem from the aspect of the strategy is not a strategy that is integrated with the company's goals. Problem from structural aspects, namely the absence of a second layer level manager or head. Problem from the aspect of the system is no system information for each activity in the company. Problem from style aspect is the absence of a successor. Problem from staff aspect is no human resource planning. The last, problem from skill aspect which is no good in recruitment process. Results from analysis using 7S McKinsey, useful also to overcome the causes of the above problems. And the results of the analysis showed that PT. Marktel need a human resource planning. Among these are getting forecasting needs for new branch office 2015-2017, which determines the best source of external recruitment to be used, the promotion, to prepare candidates for a successor. For PT. Marktel with human resource planning is expected to be able to compensate for the increasing demands of that industry.Â Keyword: Recruitment, Promotion, Succession Planning, Human Resource Planning